Video-based phase analysis of technical errors in fundamental tennis skills among physical education students - Ruslan, Ruslan; Hidayat, Joni Taufik; Alficandra, Alficandra (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2026)
Background: Technical errors frequently occur during the acquisition of fundamental tennis skills, yet limited studies have systematically examined these errors across different movement phases using video-based analysis among physical education students. Objectives: This study aimed to analyze technical errors across four fundamental tennis techniques and three movement phases using a video-based analysis approach. Methods: A cross-sectional observational study was conducted with 36 physical education students selected through purposive sampling. Participants performed forehand, backhand, volley, and serve techniques, which were analyzed using video recordings and Kinovea software. Technical errors were evaluated independently by two trained observers across the preparation, execution, and follow-through phases. Data were analyzed using descriptive statistics and inferential analysis. Results: The serve demonstrated the highest proportion of technical errors (31.1%), followed by the forehand (28.3%), backhand (26.4%), and volley (14.2%). Errors occurred most frequently during the execution phase (45.0%). Statistical analysis indicated significant differences in technical error scores among the four techniques (p < .001). Conclusion: Video-based phase analysis enabled detailed identification of technique- and phase-specific technical errors in beginner tennis performers. These findings provide evidence to support phase-specific feedback strategies and instructional planning for improving fundamental tennis skills in physical.